2018
DOI: 10.3390/su10061816
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Enterprises and the Relation between Social Performance and Financial Performance: Empirical Evidence from Korea

Abstract: Most studies on the relationship between corporate social performance (CSP) and corporate financial performance (CFP) have focused on large enterprises and archival tests for SMEs have been relatively few. There is a need for SME studies that are comparable to the research on large enterprises. In this study, we tested the CSP-CFP relationship of SMEs in Korea using a massive archival database. Although common theories on corporate social responsibility (CSR) in SMEs describe SMEs as non-strategic performers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…The implementation of a consistent KM strategy, both KM exploitation strategy and KM exploration strategy, is greatly amplified by the use of coherent PMS since the quality of decision-making increases. This is especially true for SMEs whose decision-making activities is largely influenced by the entrepreneurial decision styles and for family firms with limited professionalization on business administration [65]. This raises a managerial issue for SMEs and family businesses [152], since our findings demonstrate that the use of PMS allows SMEs to reach a higher level of economic sustainability and encourage to increase the level of professionalization in management.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The implementation of a consistent KM strategy, both KM exploitation strategy and KM exploration strategy, is greatly amplified by the use of coherent PMS since the quality of decision-making increases. This is especially true for SMEs whose decision-making activities is largely influenced by the entrepreneurial decision styles and for family firms with limited professionalization on business administration [65]. This raises a managerial issue for SMEs and family businesses [152], since our findings demonstrate that the use of PMS allows SMEs to reach a higher level of economic sustainability and encourage to increase the level of professionalization in management.…”
Section: Discussionmentioning
confidence: 69%
“…If the sustainability perspective is now universally affecting the strategic and managerial efforts of every kind of organization, the different dimensions of sustainability are significantly influenced by the operational and dimensional context. According to Choi et al [65], SMEs have a different sustainability approach compared to larger firms, due to specific organizational features, particularly linked to Due to these characteristics, the authors demonstrate that the perception of low social and environmental impacts [66] and the limited impact on stakeholders cause the following two main consequences:…”
Section: Economic Sustainability In Smesmentioning
confidence: 99%
“…In another study, this one conducted in Korea, CSR-related research has also been focused on large companies. There is a need for studies in SMEs that are comparable to research on large companies and that can compare corporate social performance with corporate financial performance [27]. Other results indicate that ethical practices have a positive impact on corporate governance, and in turn, corporate governance has a positive impact on CSR.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…Due to the small size and the potential of being more flexible and innovative, SMEs can, in fact, bring novelties to good social responsibility opportunities [23,24]. This paper focuses on the sustainability theme as this theme raises different criticisms or points of view [25,26], due to its wide content, and can be interpreted as a new model of development or just a redesign of capitalism [13,24,27,28]. Increasingly, many companies are implementing sustainability-oriented strategies; for example, it was observed that Embraer has integrated the CSR practices with other existing management systems in a harmonious and mature form [9], and in the same way, several researchers [2,13,22,25,29,30] dedicate themselves to studying this theme.However, different opinions and approaches on how to deal with issues related to sustainability are perceived in this process.…”
mentioning
confidence: 99%
“…From Carroll [41], the economic consequences have become one of the basic considerations of CSR studies. As a result, CSR researchers in recent decades have focused on the economic impacts of CSR mostly for the bigger organizations [42], but yet to reach a universal conclusion. For example, Margolis and Walsh [2] showed that less than half (54) of the 127 studies from 1972 to 2002 had reported some positive CSR-performance relationships.…”
Section: Csr As Investmentmentioning
confidence: 99%